NUMERICAL STUDY OF COMPARISON THE EFFECT OF FRICTION AND RESTITUTION COEFFICIENT ON SEPARATION EFFICIENCY OF CYCLONE - Anggara, Fajar (Universitas Muhammadiyah Jakarta, 2020)
Numerical modeling of cyclone on separation process was developed to increase the efficiency of collection. In terms of increasing the accuracy, this researsh was conducted to observe comparison in between the effect of coefficient of friction (COF) and restitution (COR) on the effeciency of colection. This reseacrh was using ANSYS 17 to simulate cyclone in 3D geometry. Where the variation of COR was 0,0.5 and 1 while the COF was 0,10,20 and 120. The result shows COR has not correspondence to the efficiency of collection but COF has inverse correspondence. Hence, the more friction on the cyclone surface, the more resistant sand particle to go down.